Public perception to littering in greenspaces: a case study in Bintulu, Sarawak, Malaysia - Abdul Aziz, Nor Akmar; Lukhman, Arief Aiman; Keen, John Chubo; Awangku Daud, Dayangku Shazana Rawaida (Institute of Physics Publishing, 2019)
Greenspaces are central to the success of cities. However, what is normally found while walking in local parks or greenspaces are empty cans, bottles, food wrappers and other litters that ruin the aesthetic beauty of the site. Increase in the number of visitors visiting parks in Malaysia has resulted in a growing littering problem. Some parks even received numerous complaints regarding litter. In order to understand the problem of littering in parks, a study was conducted with the objective of identifying factors influencing peoples’ littering behaviour in Pantai Temasya Bintulu, Sarawak, Malaysia. A total of 178 set of questionnaires were distributed to visitors at Pantai Temasya Bintulu, Sarawak, which is a popular recreational park in Bintulu. Data collected was encoded into the Statistical Package for Social Science (SPSS) and analysed accordingly. The study found more male (61.8%) than female (38.2%) respondents have done littering in the past. While more Chinese (73.1%) respondents admitted to littering than any other races. With regards to marital status, singles (64.2%) and those without children (64.4%) top the list for littering. Respondents of the age group of 17 to 25-year-old (70.6%) recorded a high percentage for littering as compared to other age groups. Respondents with only a primary school (66.7%) education have a higher tendency to litter. Besides, jobless adults and students also dominated the chart for littering for the occupation profile. Parallel with that, the income group which those without any source of income (65.3%) was the highest to admit to littering. The study identified attitude to be the highest factor influencing littering among visitors with nearly 65% respondents agreeing to it. Meanwhile, beverage containers such as aluminium cans, glass and plastic bottles were found to be the type of litter most frequently found in Pantai Temasya Bintulu. Studies on public perception towards littering are essential for administrative and strategic planning of litter control. In the case of Pantai Temasya Bintulu, early education and awareness campaigns are seen to be the best approach to instil good attitudes among the visitors.